Purchase Intention as the Intervening Variable, Amongst Customer Review, Product Quality, Korean Brand Ambassadors, and Live Promotion to Purchase Decision Making - Fadillah Putri Abadi; Vincent Didiek Wiet Aryanto; Diana Aqmala (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2024)
This investigation was undertaken to evaluate the extent to which online customer reviews, product quality, Korean brand ambassadors, and live promotions affect the purchasing decisions of Shopee consumers situated in Semarang. Furthermore, the research explores the mediating function of purchase interest within the correlation between product quality and brand ambassadors concerning purchasing decisions. A sample size of 250 participants was employed and analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that online customer reviews, product quality, brand ambassadors, and live promotions exert a positive and statistically significant influence on purchasing decisions. Moreover, purchase interest serves as a mediator in the relationship between product quality and purchasing decisions, as well as between brand ambassadors and purchasing decisions.